Influence of Air Spring Composite Parameters on Vertical Stiffness Characteristics - WANG Yan; BU Jiling; CHEN Kang; SHEN Quanan (机车电传动)
Based on the tire lift equation, nonlinear theory and fluid-solid coupling theory, an air spring system model with an auxiliary chamber was established by using finite element software ABAQUS, and the simulation results were validated by comparing with experiment datum. By changing volume of the air spring with an auxiliary chamber and standard high simultaneously, and altering volume of the auxiliary chamber and cord parameters simultaneously, to explore influence of compositive parameters on the vertical stiffness of air spring. The results showed: volume of the auxiliary chamber was larger, vertical stiffness of the air spring increased more quickly with more standard high; Without auxiliary chamber, cord layer and cord spacing had great influences on the vertical stiffness, while considering auxiliary chamber, cord layer and cord spacing hardly affected the vertical stiffness; within a certain range, no matter how much volume of the auxiliary chamber was, cord angle had great effect on the vertical stiffness.